Pathways to the past : tourism and heritage in the Little Karoo - Van Pletzen-Vos, Liezl (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DPhil (Geography and Environmental Studies))--University of Stellenbosch, 2009.